Respuesta :
Answer:
4c² + 11cd + 5d
Step-by-step explanation:
(–4c2 + 7cd + 8d) + (–3d + 8c2 + 4cd)
-4c² + 7cd + 8d - 3d + 8c² + 4cd (opening bracket)
8c²-4c²+7cd + 4cd + 8d - 3d
= 4c² + 11cd + 5d
Answer:
4c^2 + 5d + 11cd
Step-by-step explanation:
Hey next time please write the numbers that have exponent like this: (Ex: 3x^2)
(-4c^2 + 7cd + 8d) + (-3d + 8c^2 + 4cd)
Combine like terms
-4c^2 + 8c^2 = 4c^2
Combine Like Terms
7cd + 4cd = 11cd
Combine Like Terms
8d - 3d = 5d
Results:
4c^2 + 5d + 11cd
4c^2 + 5d + 11cd
Step-by-step explanation:
Hey next time please write the numbers that have exponent like this: (Ex: 3x^2)
(-4c^2 + 7cd + 8d) + (-3d + 8c^2 + 4cd)
Combine like terms
-4c^2 + 8c^2 = 4c^2
Combine Like Terms
7cd + 4cd = 11cd
Combine Like Terms
8d - 3d = 5d
Results:
4c^2 + 5d + 11cd